The Effect of Ciu Alcohol on MCV and Neutrophils in White Rats (Rattus norvegicus) - Ni Luh Larasati Puspanegari; Nuriyah Nanda Beliani; Omry Tri Asmara Adi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Alcohol consumption is a public health problem that is still a concern in various countries. One type of alcoholic beverage commonly found in the Sukoharjo area is ciu. This study aims to determine the effect of giving traditional alcohol ciu on the Mean Corpuscular Volume (MCV) value and the number of neutrophils in male white rats (Rattus norvegicus). The study used a quasy-experiment/post test design with 27 male white rats of the Wistar strain divided into three groups, namely the 0 ml ciu control group, the 2 ml ciu treatment group, and the 4 ml ciu treatment group for 14 days. Then the MCV value was examined using the Abacus 3CT Hematology Analyzer and the number of neutrophils was calculated using the diff count method. Then, the data were analyzed using the Shapiro-Wilk test, Levene's test, and One-Way ANOVA test. The outcomes revealed that there were normal and less than normal MCV values and there was an increase in the number of neutrophils. The conclusion of this investgation is that there is no effect of giving traditional ciu alcohol to male white rats (Rattus norvegicus) on MCV values and neutrophil counts.